"I'm Still Fighting for the Two of Us": How Partners of UK Veterans Construct Their Experience of Living with Combat‐Related Trauma. (7th June 2018) - Doncaster, Emily; Hiskey, Syd; McPherson, Susan; Andrews, Leanne
Abstract : There has been little qualitative research into the experiences of UK partners of veterans with PTSD. This study therefore aimed to explore how partners constructed their experiences of living with the condition. Fifteen female partners of male UK veterans were recruited and interviewed. Using a social constructionist thematic analysis, five themes were constructed: the women's need to subdue own emotional and behavioral responses; dilemmas about whether the veteran was unwell or 'bad'; attempts at negotiating multiple roles; challenging the narrative of veterans as heroes; and the relational struggle with the transition to nonmilitary life. This study highlighted the importance of considering the veteran as existing within a relational and cultural context, and the need to include partners in therapeutic interventions.